2022
DOI: 10.3389/fpsyt.2021.820598
|View full text |Cite
|
Sign up to set email alerts
|

The Sensory Abnormality Mediated Partially the Efficacy of Repetitive Transcranial Magnetic Stimulation on Treating Comorbid Sleep Disorder in Autism Spectrum Disorder Children

Abstract: Sleep disorder emerges as a common comorbidity in children with autism spectrum disorder (ASD), and the interaction between the core symptoms of ASD and its sleep disorder remains unclear. Repetitive transcranial magnetic stimulation (rTMS) was used on the bilateral dorsolateral prefrontal cortex (DLPFC) to investigate the efficacy of rTMS on the core symptoms of ASD and comorbid sleep problems as well as the mediation role of the ASD symptoms between rTMS intervention and sleep improvement. A total of 41 Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
0
10
0
6
Order By: Relevance
“… 19 , 27 In summary, low-frequency rTMS stimulation of the right DLPFC has been shown to have an intervention effect by modulating the anterior cingulated cortex connectivity in the meso-cortical-limbic circuit and the GABAergic and glutamatergic circuitries. 28 , 29 , 30 rTMS has not been used for a long time in the treatment of ADHD and its comorbidities, but reports of adverse side effects of rTMS are uncommon. Occasionally, pressure and allergies due to the device being worn on the head have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 27 In summary, low-frequency rTMS stimulation of the right DLPFC has been shown to have an intervention effect by modulating the anterior cingulated cortex connectivity in the meso-cortical-limbic circuit and the GABAergic and glutamatergic circuitries. 28 , 29 , 30 rTMS has not been used for a long time in the treatment of ADHD and its comorbidities, but reports of adverse side effects of rTMS are uncommon. Occasionally, pressure and allergies due to the device being worn on the head have been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 17 , 19 Repetitive transcranial magnetic stimulation has been shown to be effective for SD in adult patients with ADHD and comorbid SD in children with autism spectrum disorders. 19 , 20 , 21 , 32 Therefore, it is a promising approach to SD intervention for children, especially preschool (4-6 years) children with ADHD. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The consequences of abnormal behavior during the day can negatively impact the quality of sleep, resulting in a vicious cycle. Additionally, sleep disorders have a greater impact on obesity, injuries, and attention deficit in children with ASD than in other children ( 11 , 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The right DLPFC is known as one part of the socially related brain areas, plays a crucial role in the integration of goals and the reward system, has been found the weak responses in ASDs and selected for treating primary insomnia with good effects ( 23 , 24 ). In addition, another study using 25% MT for the treatment of ASD found that it could alleviate sleep disturbances with little adverse effects ( 29 ). In this ongoing clinical trial, 1 Hz rTMS at 50% RMT (50 trains of 30 pulses, with a 3-s interval between each, leading to a sum of 1,500 pulses) will be applied over the right DLPFC.…”
Section: Methods and Analysismentioning
confidence: 99%
“…However, the implications of rTMS for insomnia in ASD patients have not been fully established. Only one study indicated that rTMS can alleviate sleep disturbances in ASD, which were assessed by the Children's Sleep Habits Questionnaire (CSHQ) ( 29 ). No randomized, double-blind, controlled studies were conducted to evaluate the efficacy of rTMS for insomnia through objective assessments such as PSG or actigraphy.…”
Section: Introductionmentioning
confidence: 99%